Pelatihan Pembuatan Lilin Aromaterapi Berbasis Minyak Serai di IKM CV Amna Lab. Aromaterapi Kabupaten Solok - Elda Pelita; Hazil Anwar; Regna Tri Jayanti; Desniorita Desniorita; Rita Youfa; Jerry Jerry; Roswita Roswita (Journal of Industrial Community Empowerment, 2022)
CV. Amna Lab Aromaterapi Small and Medium Enterprises have started the citronella oil business in 2018. Some of its products such as soap, aromatherapy spray, propolis, and body oil have arrived in several big cities in Indonesia. However, since the Covid-19 pandemic, these SMEs have experienced difficulties, especially regarding the large capital costs and the price of citronella which has fallen drastically to 100% of the original price. Under these conditions, SMEs are constrained in the process of increasing productivity and lack production technology as well as marketing and management. The Community Service Team of the ATI Padang Polytechnic offers solutions to overcome these problems by providing alternative processing of citronella oil-based products to be aromatherapy candles and educating the SMEs on the product marketing strategies through e-commerce applications. The community service team tried resolving the delinquent by determining the amount of citronella oil that should be included and the composition variations of stearic acid, vegetable oil, and paraffin. The variations were tested in order to find the right comparison in making aromatherapy candles based on citronella oil. The team also searched and studied several references to analyze marketing strategies in accordance with SMEs CV. Amana Aromatherapy Lab. Considering the result of the experiments, it was identified that 1% of citronella oil could be added to the wax mixture while the exact composition of oil and paraffin was 1: 2. The stearic acid was unsuitable to applied since the candle product easily melted. E-commerce marketing strategies were used by utilizing advertisements on internet searches to expand the promotions.